2017
DOI: 10.1111/jfs.12375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mentha spicata essential oil on chemical, microbial, and sensory properties of minced camel meat during refrigerated storage

Abstract: The aim of the present study was incorporation of Mentha spicata essential oil (MSO) at three different concentrations (0.5, 1, and 1.5% vol/wt) into raw minced camel meat to extend shelf life and evaluate its antibacterial activity against Listeria monocytogenes for 12 days at refrigerated temperature. Final microbial population (total mesophilic and psychrotrophic bacteria, Pseudomonas spp., Enterobacteriaceae, and L. monocytogenes) decreased approximately 1-4 log CFU/g in treated samples compared to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The effect of EOs on the results of sensory evaluation was largest in the case of the odor of raw meat. Other authors also observed the beneficial effects of adding EOs on the odor of such products as minced sheep meat, chicken breast meat, minced camel meat and minced beef (Govaris et al, 2010;Chouliara et al, 2007;Shahbazi et al, 2018;Skandamis and Nychas, 2001). Data in Table 4 indicate that the effect obtained may result not only from the masking effect of these additives, but also from the fact that they can directly limit the formation of some compounds.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The effect of EOs on the results of sensory evaluation was largest in the case of the odor of raw meat. Other authors also observed the beneficial effects of adding EOs on the odor of such products as minced sheep meat, chicken breast meat, minced camel meat and minced beef (Govaris et al, 2010;Chouliara et al, 2007;Shahbazi et al, 2018;Skandamis and Nychas, 2001). Data in Table 4 indicate that the effect obtained may result not only from the masking effect of these additives, but also from the fact that they can directly limit the formation of some compounds.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, the oils used were selected as acceptable in turkey meat in the preliminary sensory evaluation. One of the effects of adding EOs to meat may be an improvement in its odor during refrigerated storage (Govaris et al, 4 2010;Chouliara et al, 2007;Shahbazi et al, 2018;Skandamis and Nychas, 2001). The effect observed may be due to both masking the spoiled meat odor by the added volatile substances and the direct influence of EO components on the chemical, biochemical and microbial reactions, resulting in the formation of components of the odor of spoilage.…”
mentioning
confidence: 99%
“…Fresh garlic was reported to impart antioxidant and antimicrobial effects at 40g/kg in camel meat. Shahbazi et al [85] also reported that essential oil from Mentha spicata at concentrations of 0.5% and 1% improved preservation of camel meat without developing any unfavourable organoleptic properties. Incorporation of ginger improved the physicochemical and sensory properties of camel burgers [86].…”
Section: Effect Of Pretreatmentsmentioning
confidence: 99%
“…C. jejuni (NCTC 11168) was obtained from the Department of Microbiology, School of Medicine at Kermanshah University of Medical Sciences, cultured in the BHI broth at the temperature of 37 ± 1 °C overnight, and diluted to 5 (high) and 3 log CFU/ml (low) using a tenfold serial dilution in 0.1% peptone water for further experimentation [29].…”
Section: Preparation Of Campylobacter Jejunimentioning
confidence: 99%